2022
DOI: 10.1186/s12931-022-02060-3
|View full text |Cite
|
Sign up to set email alerts
|

Association between dexamethasone treatment and the host response in COVID-19 patients admitted to the general ward

Abstract: Dexamethasone improves clinical outcomes in COVID-19 patients requiring supplementary oxygen. We investigated possible mechanisms of action by comparing sixteen plasma host response biomarkers in general ward patients before and after implementation of dexamethasone as standard of care. 48 patients without and 126 patients with dexamethasone treatment were sampled within 48 h of admission. Endothelial cell and coagulation activation biomarkers were comparable. Dexamethasone treatment was associated with lower … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…IL-6 and TNF-alpha (TNF-α)) that may be affected by targeting CD14. 17 , 18 , 19 , 20 Presepsin, an N-terminal fragment of full length CD14 that is generated in the setting of CD14-dependent innate immune activation, and a marker of CD14 signaling, 9 , 21 has been associated with clinical outcomes in observational studies of patients with severe COVID-19. 22 , 23 , 24 , 25 , 26 In early phase clinical trials in bacterial sepsis and ARDS, IC14 reduced systemic inflammation (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…IL-6 and TNF-alpha (TNF-α)) that may be affected by targeting CD14. 17 , 18 , 19 , 20 Presepsin, an N-terminal fragment of full length CD14 that is generated in the setting of CD14-dependent innate immune activation, and a marker of CD14 signaling, 9 , 21 has been associated with clinical outcomes in observational studies of patients with severe COVID-19. 22 , 23 , 24 , 25 , 26 In early phase clinical trials in bacterial sepsis and ARDS, IC14 reduced systemic inflammation (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Although this bias is inevitable in our design, its impact may be relatively modest. We previously showed that corticosteroid treatment given shortly before sampling only minimally affects plasma biomarkers ( 44 ). In addition, the proportion of patients receiving corticosteroids before sampling was similar between clusters and had no significant value in predicting cluster membership based on clinical variables ( see Table E9).…”
Section: Discussionmentioning
confidence: 99%
“…With regard to COVID-19, two studies showed results that were consistent with our study. In the first, for patients admitted to the general ward with lower severity scores than in our study, DXM that was administered within 19 h of collection reduced plasma IL-6 and IL-1ra levels but did not influence COVID-19 coagulation disorders [ 45 ]. In the second, for patients admitted to intensive care, DXM decreased plasma levels of cytokines (IL-1, IL-2, IL-6, IL-8, IL-10, IL-17, IFNγ, and MIP-1) and endothelial markers but biomarkers of coagulopathy were not measured [ 35 ].…”
Section: Discussionmentioning
confidence: 99%